Implementation Of Law Number 40 Of 2007 On Corporate Social Responsibility (Csr) At Pt. Sinar Bengkulu Inti Mulya - Qawi, Ari Mughni; Lorita, Evi; Imanda, Antonio (Utami Publisher, 2025)
This study aims to understand the implementation of Law Number 40 of 2007 regarding Corporate Social Responsibility (CSR) at PT. Sinar Bengkulu Inti Mulya. The research employed a descriptive qualitative method, utilizing observation, interviews, and documentation. The study involved three informants, consisting of one key informant and two primary informants. Results indicated that CSR implementation at PT. Sinar Bengkulu Inti Mulya complies with existing regulations through six main indicators: mandatory CSR implementation, CSR budget allocation, CSR program focus, implementation impact, implementation reports, and regulatory compliance. CSR programs were consistently implemented twice annually, effectively addressing community needs, and positively impacting local social and economic conditions. The company regularly reported its CSR activities every six months to the local administration, demonstrating its accountability and commitment to social responsibility.